ANALYSIS OF COMPOSITE STOCK PRICES ASEAN+3 DEVELOPED COUNTRIES ON INDONESIAN IDX COMPOSITE: IS THERE ANY CONTRIBUTION EXIST? - Rizki Maulana Prasetyo; Dyta Pranatasari; Mia Asyiroh; Iis Sumiati; Dayat Hidayatullah; Hanifah Dwi Ramandhani (LP2M Universitas Bina Bangsa, 2024)
This research explores the intricate connections between global stock indices and how they affect each other, as determined by Granger Causality and Variance Decomposition analyses. The analysis highlights the prominence of the Shanghai Composite Index (SHCOMP) of China by showing that it has a notable influence on other indexes. It is noteworthy that the Korean KOSPI has little effect on the Indonesian IHSG, whereas the Indonesian IHSG has a notable influence on Japan's NIKKEI 225. On the other hand, the Chinese IHSG is significantly impacted by the Korean KOSPI. With a 5% margin of error, the study extends its forecast over a 30-year timeframe and finds notable trends in the third phase. The Indonesian IDX Composite's movement is 6.5% influenced by the NIKKEI 225 at this time. and the KOSPI makes a noteworthy 10.9% contribution to the same movement. These results highlight the crucial role China's SHCOMP plays in illuminating the complex interactions between global stock indices